Preparation of low temperature titanium dioxide thin films by using doctor-blade method / Nurafiqah Husna Abdul Rashid - Abdul Rashid, Nurafiqah Husna (Faculty of Applied Sciences, 2017)
The Ti02 films have been deposited onto a glass slide using the doctor-blade technique as-deposited and annealed in different low annealing temperature at 120 DC, 140 DC, 160 DC and 400 DC. The structural and optical properties of prepared Ti02 thin films was proved by using XRD and UV-vis spectrometer that effected by annealed process. The XRD analysis as-deposited Ti02 thin film and Ti02 thin film annealed at 140°C. Optical properties of Ti02 thin film measured by UV-vis at the annealing temperature from 120°C - 400 DC. Besides, the band gap value measured by Tauc plot.